2021
DOI: 10.1038/s41598-020-80264-7
|View full text |Cite
|
Sign up to set email alerts
|

Integrated mRNA and miRNA expression profile analysis of female and male gonads in Hyriopsis cumingii

Abstract: Hyriopsis cumingii is an important species for freshwater pearl cultivation in China. In terms of pearl production, males have larger pearls and better glossiness than females, but there are few reports focusing on the sex of H. cumingii. In this study, six mRNA and six microRNA (miRNA) libraries were prepared from ovaries and testes. Additionally, 28,502 differentially expressed genes (DEGs) and 32 differentially expressed miRNAs (DEMs) were identified. Compared with testis, 14,360 mRNAs and 20 miRNAs were up… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 87 publications
(83 reference statements)
0
9
0
Order By: Relevance
“…microRNAs (miRNAs) are an important class of endogenous factors with the ability to regulate the expression of protein-coding genes. In recent years, it has been found that its role in testicular development and spermatogenesis has become more and more extensive [ 20 , 21 ]. They involved in various biological processes such as male germ cell differentiation, gonadal oxidative stress, and testicular immune homeostasis through targeted inhibition of gene expression [ 22 , 23 ], and can be considered as crucial regulators of biological processes [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…microRNAs (miRNAs) are an important class of endogenous factors with the ability to regulate the expression of protein-coding genes. In recent years, it has been found that its role in testicular development and spermatogenesis has become more and more extensive [ 20 , 21 ]. They involved in various biological processes such as male germ cell differentiation, gonadal oxidative stress, and testicular immune homeostasis through targeted inhibition of gene expression [ 22 , 23 ], and can be considered as crucial regulators of biological processes [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…The HMG domain-containing transcription factor sox9 plays an important role not only in testis-determining pathways of mammals and birds but also in male gonad differentiation and maintenance ( Da silva et al, 1996 ). In Hyriopsis cumingii ( Wang et al, 2021 ), Pinctada margaritifera ( Teaniniuraitemoana et al, 2014 ) and Sinonovacula constricta ( Yao et al, 2021 ), sox9 also has been reported as a possible sex determination or sex differentiation gene. The Cgsoxh , homolog of the sox9 in Crassostrea giga , was considered to be a regulator of Cgdsx and Cgfolx2 , directly or indirectly affecting their interaction ( Zhang et al, 2014 ).…”
Section: Discussionmentioning
confidence: 99%
“…The notch signaling cascade, mediated by the notch gene encoding transmembrane receptors, is another important pathway involved in basic processes such as cell proliferation, stem cell maintenance, and differentiation during embryonic and adult development in animals [57]. The notch signaling pathway has been shown to regulate sexual differentiation in the mollusks Hyriopsis cumingii and Crassostrea hongkongensis [58,59]. In the current transcriptome study of M. unguiculatus, the enrichment of these pathways suggests their potential involvement in the regulation of gonad development in this species.…”
Section: Analysis Of Kegg Enrichment Pathwaysmentioning
confidence: 99%